Vitamin D: a brief overview of its importance and role in inflammatory bowel disease - Mudambi, Kiran; Bass, Dorsey (Translational Gastroenterology and Hepatology, 2018)
Vitamin D has traditionally been known for its regulation of bone metabolism and homeostasis, but emerging evidence suggests that it also has a broad function in immune regulation, and inflammatory bowel disease (IBD). The etiology of IBD is thought to be multifactorial but stems in part due to the deregulation of the immune response to environmental factors in the setting of a pre-existing genetic disposition. Vitamin D, based on its mechanistic role at the cellular level in T-cell trafficking, had been postulated to have a direct effect on the immune system, This alludes to the fact that vitamin D may have the ability to not only potentiate the IBD phenotype, but also in doing so, its supplementation may serve a therapeutic role in amelioration of the diseased state. We review in this article the current literature as it pertains to the basic mechanism of Vitamin D, its role in the pathogenicity of IBD, how it regulates our immune system, interpretation and accuracy of obtaining levels, and the role there may be in supplementation in IBD.